2015
DOI: 10.2147/jir.s76304
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammatory markers and poor outcome in diabetic patients presenting with ST segment elevation myocardial infarction

Abstract: ObjectiveCarbohydrate metabolism disorders (CMD) significantly impact the development and progression of all forms of ischemic heart disease, and inflammation is regarded as a general pathogenetic link between CMD and ischemic heart disease.MethodsA total of 601 patients with ST segment elevation myocardial infarction (MI) (STEMI), admitted within 24 hours from the onset of symptoms during 1 year, were included in this registry study. The blood levels of inflammation markers were measured at days 10–14 with fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…These findings may suggest that different settings may be regulated by different cytokine production pathways and that IL-6 together with IL-6R has a biological role in susceptibility to CAD. It is also known that the balance between pro-inflammatory and anti-inflammatory markers has a critical role in the development of CAD 1921. In this direction, different sets of epidemiological studies have revealed that specific SNPs in different genes, such as IL-6, IL-16, IL-17, IL-18, and IL-23, are associated with the development of CAD 2228.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may suggest that different settings may be regulated by different cytokine production pathways and that IL-6 together with IL-6R has a biological role in susceptibility to CAD. It is also known that the balance between pro-inflammatory and anti-inflammatory markers has a critical role in the development of CAD 1921. In this direction, different sets of epidemiological studies have revealed that specific SNPs in different genes, such as IL-6, IL-16, IL-17, IL-18, and IL-23, are associated with the development of CAD 2228.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the balance between pro-inflammatory and anti-inflammatory markers has a critical role in the development of CAD. 19 21 In this direction, different sets of epidemiological studies have revealed that specific SNPs in different genes, such as IL-6, IL-16, IL-17, IL-18, and IL-23, are associated with the development of CAD. 22 28 The results from this research, regarding T allele from rs2069860, associated with the patients without CAD, suggest that rs2069860 is typical for the development of hypertension or diabetes mellitus type II but not for CAD.…”
Section: Discussionmentioning
confidence: 99%